STRUCTURAL EQUATION MODEL (SEM)-PREDICTING SHOPPERS SHOPPING EXPERIENCE IN MALLS - Gangisetty, Dr. N.; Mohana, Dr. S. (The journal of contemporary issues in business and government, 2022)
Purpose: This paper aims to explore the composition of “ Shopping Experience” for shoppers inshopping malls of South India. Research Methodology: The paper applies analyzing data using Reliability Test, Confirmatory Factor Analysis (CFA) and Multiple Linear Regression on a sample of 356 respondents and reduces a set of 18 variables into a list of six attributes of shopping malls. Finding: The present study proposes a model of the impact of shopping mall attributes on shopping experience of shoppers. Implication: The study found that convenience, aesthetic, security, safety, amenities and tenants are impacting significantly the shopping experience. Therefore, shopping mall managers should focus on the above factors to provide enrich shopping experience of shoppers. Conclusion: The study investigated the impact of mall attributes on shopping experience in malls of the shoppers concluded that convenience had the highest impact on the shopping experience of the shoppers followed by, aesthetic, security, safety, amenities and tenants.